2010
DOI: 10.1089/jpm.2009.0166
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Outcomes and Survival of Patients with Advanced Cancer Admitted to an Acute Palliative Care Unit at a Comprehensive Cancer Center

Abstract: Our APCU serves patients with advanced cancer with diverse clinical characteristics and survival, and discharged home a significant proportion with survival greater than 6 months. RESULTS from this simultaneous care program suggest a pattern of care different from that of traditional hospice and palliative care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 32 publications
3
91
1
3
Order By: Relevance
“…Based on the literature, the presence of these signs indicates a survival of weeks or less [11,20,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the literature, the presence of these signs indicates a survival of weeks or less [11,20,29].…”
Section: Discussionmentioning
confidence: 99%
“…Both APCUs have access to full arrays of diagnostic and therapeutic measures, such as computed tomography and intravenous antibiotics. The historical in-hospital mortality rate was 30% at MDACC and 70% at BCH [11].…”
Section: Study Setting and Criteriamentioning
confidence: 97%
“…Previous studies have described some of the factors associated with mortality in hospitalized patients receiving palliative care consultation, [6][7][8] however, no study examined factors by site of consultation. We found that factors associated with in-hospital death varied by site of consultation for elderly patients receiving palliative care consultation.…”
Section: Discussionmentioning
confidence: 99%
“…The median length of stay is 7 days and approximately 70% of the patients are discharged alive. 12 The median survival from admission to death is 21 days. This unit was established following the structure of the palliative care unit in Edmonton, and it has in turn been a template for multiple other institutions in the United States and around the world.…”
Section: The Acute Palliative Carementioning
confidence: 99%